Acute sacroiliitis. Issue 4 (April 2016) - Slobodin, Gleb; Rimar, Doron; Boulman, Nina; Kaly, Lisa; Rozenbaum, Michael; Rosner, Itzhak; Odeh, Majed
Abstract The purpose of this study was to review the data on the etiology, risk factors, clinical presentations, and diagnosis of acute sacroiliitis. A Pubmed search utilizing the indexing term "acute sacroiliitis" was conducted and the data pertinent to the aim of the review was extracted and organized in accordance with the preplanned structure of the manuscript. The diagnosis of acute sacroiliitis is often challenging because of both the relative rarity of this presentation and diverse character of acute sacroiliac pain, frequently mimicking other, more prevalent disorders. Technetium bone scintigraphy can localize the disease process to the sacroiliac joint, while computed tomography or magnetic resonance imaging can be used for the detailed characterization and the extent of the disease as well as the diagnosis of complications. Pyogenic sacroiliitis is by far the most common cause of acute sacroiliitis. Brucellosis, acute sacroiliitis in the course of reactive arthritis, and crystalline-induced sacroiliitis frequently imitate pyogenic sacroiliitis. Acute sacroiliitis can rarely be also related to hematological malignancies or treatment with isotretinoin. Awareness to the possibility of acute sacroiliitis and a thorough physical examination are the necessary prerequisites to its timely diagnosis, while the appropriate laboratory and imaging studies should confirm the precise diagnosis and direct the appropriate treatment strategy.